Alternative View of Unemployment Issue among Saudi Citizens - Automatization of Local Gas Stations as a Case Study - Yousif, Mohammed Ahmed Al (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The primary objective of this paper is to propose an alternative solution for unemployment among Saudi youth. This paper seeks to address the problem of unemployment in Saudi Arabia from a different perspective: productivity aspect. Substantially, this paper proposes solutions for the Saudi youth unemployment problem by increasing the non-oil private sector’s productivity. It evaluates the macroeconomic gains of the proposed solutions, such as the number of new jobs for Saudi citizens and additional value-added. The research’s main hypothesis is that increasing the non-oil private sector’s productivity would significantly reduce unemployment among Saudi citizens. There are two methodologies for evaluating the expected economic benefits of increasing productivity in local economic activities. The first methodology, which is the Saudization of local gas stations by transforming the local gas stations into self-service ones (with one cashier every 8 hours for each gas station), finds that there would be more than 28,000 new jobs with reasonable salaries (at least SAR 3000 instead of SAR 1000 for at least 5 low-skilled foreign laborers) for unemployed Saudi citizens, which are socially accepted and at no additional cost to the government. The second methodology uses Leontief’s IO model to estimate the macroeconomic effects of increasing productivity in the non-oil private sector. It finds that the Saudi gross domestic product (GDP) is expected to record an additional growth rate of around 2.7 percentage points (Note 1) and to create more than 96,000 sustainable jobs for Saudi citizens within the period from 2021 to 2025.